Dre Parker's Effort To Be Respected And Not To Be Abused In Karate Kid (2010) Directed By Harald Zwart: An Individual Psychological Approach - WATI, AMINA (2012)
The purpose of this study is to reveal Dre's effort reflected in Karate Kidmoviedirected by Harald wartpublished in 2010. The objective of the study is to analyze the structural elements in the movie and to analyze the effort based on Individual Psychological approach. The object of the study is a movie Karate Kid directed by Harald Zwart. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie and script of Karate Kidand the secondary data source is information related to the primary data source, and website. The method of collecting data is observation and library review. The method of analyzing data is descriptive technique. The results of the study show that: first, based on the structural analysis,Harald Zwartwants to deliver a message that every human must be respected and not to be abused.Second,based on the Individual Psychological analysis, Harald Zwartreflects Dre Parker effort by presenting Marxist issues in this movie,akid works hard and struggle for it.